A meta-analysis of top management team compositional characteristics and corporate innovation in China. Issue 1 (1st January 2021) - Wei, Xuhua; Yang, Huan; Han, Siyi
ABSTRACT: Although a large number of empirical studies have explored the relationship between top management team (TMT) compositional characteristics and corporate innovation in China, there is much controversy regarding which kind of TMT compositional characteristic can better promote corporate innovation during the economic transition period. To reconcile these theoretical contradictions and explain why the empirical research results are inconsistent, we meta-analysed the effects of TMT compositional characteristics (i.e. variety, disparity and faultlines) on corporate innovation in China and explored the potential moderators between TMT compositional characteristics and corporate innovation. Based on 234 effect sizes reported in 89 studies (35, 515 TMTs), we found that TMT composition types (i.e. task- and relation-oriented dimensions) could significantly moderate the relationship between TMT compositional characteristics and corporate innovation. Compared to TMT relation-oriented variety and disparity, TMT task-oriented variety and disparity were more positively related to Chinese corporate innovation. Further, TMT task-oriented faultline strength was positively related to Chinese corporate innovation, whereas TMT relation-oriented faultline strength was negatively related to it. Our findings not only help researchers understand why the relationship between TMT compositional characteristics and corporate innovation is inconsistent, but also help corporations in the backdrop to the economic transition to promote innovation by improving their TMT composition.